3D‐printing antibacterial composite filaments containing synergistic antibacterial activity of green tea and tannic acid. (8th August 2021) - Thavornyutikarn, Boonlom; Lertwimol, Tareerat; Kosorn, Wasana; Hankamolsiri, Weerawan; Nampichai, Nutdanai; Janvikul, Wanida
Abstract: Novel three‐dimensional (3D) printing antibacterial thermoplastic polyurethane/green tea/tannic acid (TPU/GT/TA) composite filaments were successfully developed. The antimicrobial property of the filaments was evaluated against three Gram‐positive bacterial strains, that is, Staphylococcus aureus, Staphylococcus epidermidis, and Bacillus subtilis, using an agar diffusion assay. It was noted that the enhanced inhibitory potency of the filaments was derived from the synergistic antibacterial activity of GT and TA, also confirmed by the antibacterial potency of the crude extract of GT/TA mixture which was used as a synergism study model. Not only the weight ratio of GT and TA incorporated in the filaments, but also the uniform mixing of the polymer compounds played a crucial role in the antibacterial efficiency of the resulting filaments. Both GT and TA were uniformly distributed in the matrices of filaments composed of total contents of GT and TA ≤ 30 wt%, proven by scanning electron microscopy (SEM), energy dispersive X‐ray spectroscopy (EDX), and micro‐computer tomography (μCT) analysis. Furthermore, a number of voids existed in the filament matrix were found to increase with a rising content of fillers. Among the composite filaments prepared, TPU/GT25 /TA:70/10/20 filament demonstrated the best tensile property, whereas TPU/GT25 /TA:70/15/15 filament possessed the greatest inhibitory potency. The antibacterial stability of the developed composite filaments after 3D printing and storage was eventually assessed. The novel composite filaments had a promising potential use as an effectively antibacterial FDM feedstock for such applications as 3D printed antimicrobial insoles.